Interleaved and simultaneous multi‐nuclear magnetic resonance in vivo. Review of principles, applications and potential. (27th April 2022) - Lopez Kolkovsky, Alfredo L.; Carlier, Pierre G.; Marty, Benjamin; Meyerspeer, Martin
Abstract : Magnetic resonance signals from different nuclei can be excited or received at the same time, rendering simultaneous or rapidly interleaved multi‐nuclear acquisitions feasible. The advan‐tages are a reduction of total scan time compared to sequential multi‐nuclear acquisitions or that additional information from heteronuclear data is obtained at thesame time and anatomical position. Information content can be qualitatively increased by delivering a more comprehensive MR‐based picture of a transient state (such as an exercise bout). Also, combiningnon‐proton MR acquisitions with 1 Hinformation (e.g., dynamic shim updates and motion correction) can be used to improve data quality during long scans and benefits image coregistration. This work reviews the literature on interleaved and simultaneous multi‐nuclear MRI and MRS in vivo. Prominent use cases for this methodology in clinical and research applications are brain and muscle, but studies have also been carried out in other targets, including the lung, knee, breast and heart. Simultaneous multi‐nuclear measurements in the liver and kidney have also been performed, but exclusively in rodents. In this review, a consistent nomenclature is proposed, to help clarify the terminology used for this principle throughout the literature on in‐vivo MR. An overview covers the basic principles, the technical requirements on the MR scanner and the implementations realised either by MR system vendors or research groups, from the early days until today. Considerations regarding the multi‐tuned RF coils required and heteronuclear polarisation interactions are briefly discussed, and fields for future in‐vivo applications for interleaved multi‐nuclear MR pulse sequences are identified. Abstract : MR signals from different nuclei can be excited or received at the same time, rendering simultaneous or interleaved multi‐nuclear acquisitions feasible. This has been used in vivo to reduce the total scan time, to acquire multi‐parametric data during a transient physiological state or to improve non‐proton MR data quality with 1 H navigators. The principles and the technical implementation of this technique, from the early days until today, are presented, and clinical and research applications are discussed.